Do signatory auditors with tax expertise facilitate or curb tax aggressiveness? - DeFond, Mark; Qi, Baolei; Si, Yi; Zhang, Jieying (Journal of Accounting and Economics, 2025)
Prior research concludes that tax-expert auditors facilitate tax aggressiveness. However, these studies examine auditors who also provide non-audit tax services to their clients, creating conflicting incentives. We predict that tax-expert auditors, who do not provide non-audit tax services, reduce tax aggressiveness, because tax aggressiveness imposes costs on them. We test our prediction using Chinese data, allowing us to identify Certified Tax Agents as tax-expert auditors. We find that companies are less tax aggressive when their signatory auditor is a tax-expert who does not provide non-audit tax services. Consistent with a causal relation, a decrease in tax rates, which reduces clients’ incentives to be tax aggressive, weakens the effect of tax-expertise on tax aggressiveness. Moreover, tax-expert auditors attenuate the type of tax aggressiveness that results in tax-related misstatements. Overall, by examining auditors who do not provide non-audit tax services, we find that tax-expert auditors curb tax aggressiveness, contrary to prior research.